Understanding non-participation in a remote exercise trial among breast cancer survivors undergoing adjuvant endocrine therapy: a cross-sectional survey - Henrique Ims Bortolozo; Miguel Soares Conceição; Valeria L. G. Panissa; Marina L. V. Ferreira; Olivia M. Ruberti; Luis Otávio Sarian; Guilherme D. Telles; Felipe C. Vechin; Sophie Derchain (Sport Sciences for Health, 2026)
Abstract Purpose Despite wider access to remote/home-based exercise, many breast cancer survivors still decline structured programs. We analyzed the sociodemographic/clinical profile of women on adjuvant endocrine therapy who declined an online exercise intervention and explored their reasons for non-participation. Methods This ancillary cross-sectional survey was nested within a registered parent randomized trial (ReBEC RBR-3tqb39m). Ninety-eight women on adjuvant endocrine therapy were contacted; 25 were not reached. Of the 73 screened, 4 were excluded before randomization and 39 provided written consent and were randomized to supervised online or unsupervised home-based training. The 30 women who declined the intervention were invited to this survey; 21 completed questionnaires covering reasons for non-participation, physical activity (IPAQ), fatigue (FACT-F), and breast cancer-specific health-related quality of life (FACT-B). Decliners were compared with acceptors at baseline. Results Decliners reported significantly higher physical activity levels than acceptors (IPAQ 3108 [1840–5139] vs. 2046 [960–4216] MET-min/week; p = 0.04). A trend toward better fatigue scores was observed in decliners (FACT-F 134 [114–140] vs. 118 [99.5–131]; p = 0.06) while breast cancer-specific health-related quality of life was similar between groups (FACT-B 113 [92–122] vs. 110 [92–118.5]; p = 0.332). The most frequent reasons for declining were already being physically active (52%) and a lack of time for in-person assessments (48%), despite the remote delivery of the program. Sociodemographic variables and endocrine therapy type were not associated with participation. Conclusions Even with remote formats, enrollment may be hindered by perceived physical self-sufficiency and assessment logistics. Tailoring recruitment to individual motivations and offering remote assessment options when possible may enhance program uptake. For women already exercising, recognizing existing routines and providing ways to monitor progress may support effectiveness and sustained benefits. Parent trial registration RBR-3tqb39m (ReBEC).